2002
DOI: 10.1524/ract.2002.90.9-11_2002.597
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and dissolution studies of UO2 containing α-emitters

Abstract: Leaching / Radiolysis / XPS / alpha-doped UO 2 / PlutoniumSummary. Corrosion and dissolution of UO 2 doped with short-lived α-emitters, the so called α-doped UO 2 , was investigated in leaching experiments combined with X-ray Photoelectron Spectroscopy (XPS) analyses. These experiments are part of an ongoing set of tests aiming at evaluating the effects of α-radiolysis on the dissolution of the UO 2 spent fuel matrix when it will become exposed to groundwater in a deep final repository. Pellets of UO 2 contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Most experimental studies that investigate the effect of activity on SNF matrix dissolution kinetics focus on "old" spent nuclear fuel, which is dominated by α-emitters (e.g. [97,[115][116][117][118][119][120][121]. Poinssot et al reviewed the large experimental dataset and drew the following major conclusions on the SNF matrix dissolution kinetics [111,122,123]:…”
Section: Radionuclide Release Due To Corrosion Of the Uo 2 Matrixmentioning
confidence: 99%
“…Most experimental studies that investigate the effect of activity on SNF matrix dissolution kinetics focus on "old" spent nuclear fuel, which is dominated by α-emitters (e.g. [97,[115][116][117][118][119][120][121]. Poinssot et al reviewed the large experimental dataset and drew the following major conclusions on the SNF matrix dissolution kinetics [111,122,123]:…”
Section: Radionuclide Release Due To Corrosion Of the Uo 2 Matrixmentioning
confidence: 99%
“…Several different types of materials have been manufactured and tested in dissolution experiments. UO 2 doped with α-emitting nuclides [51][52][53][54][55][56][57][58] has been used to mimic the radiation field from spent nuclear fuel older than 1000 years. UO 2 has been doped with Pd particles [59,60] to mimic the effect of ε-phase particles (fission products forming noble metal inclusions in the fuel matrix) and with rare earth oxides [61][62][63] to mimic the effect of fission products forming oxides in the fuel matrix.…”
Section: Kinetics Of Surface Reactionsmentioning
confidence: 99%
“…Despite the 100-fold difference in the alpha activity of the two types of investigated specimen, no significant difference was observed in the dissolution behavior of uranium for the two doped materials. More recently, Cobos et al [7] showed a flux dependence between the uranium release in solution and the alpha activity of identical batches. Beyond the flux dependence, the behavior uranium in solution and the concentrations reached during tests performed without solution renewal also appear to be highly dependent on the series of experiments considered, even for batches of comparable activity alpha [14].…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of a polycrystalline UO 2 surface under alpha irradiation in contact with water has been widely investigated experimentally in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14], motivated by the prospect of direct disposal of spent fuel in a deep geological repository. In this regard it is worth remembering that over the long term, alpha radiolysis of water, which produces oxidizing and reductive species, radicals (HO • , O 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation